2011
DOI: 10.1038/oby.2010.167
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Body Composition and Pulmonary Function in Elderly People: The Korean Longitudinal Study on Health and Aging

Abstract: The age‐related increase in body fat and decrease in muscle mass are associated with increased morbidity in elderly populations. Pulmonary function also decreases with age, but no study has investigated whether regional body composition is associated with pulmonary function in an older population. The Korean Longitudinal Study on Health and Aging is a community‐based cohort study of people aged >65 years selected by random stratified sampling. Anthropometrics, biochemical factors, and lung function by spiromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…Thirdly, the assessment values of DXA and anthropometric fat measurements were compared. Relative to anthropometric measures, DXA-derived measures are more accurate and could provide more information to understand the associations of regional fat with potential health risks [39,40]. The present study suggested that %TF and android/gynoid fat ratio were better predictors than WC in normal BMI women.…”
Section: Discussionmentioning
confidence: 62%
“…Thirdly, the assessment values of DXA and anthropometric fat measurements were compared. Relative to anthropometric measures, DXA-derived measures are more accurate and could provide more information to understand the associations of regional fat with potential health risks [39,40]. The present study suggested that %TF and android/gynoid fat ratio were better predictors than WC in normal BMI women.…”
Section: Discussionmentioning
confidence: 62%
“…CT can distinguish between visceral and subcutaneous fat, and has been useful in measuring fat or muscle distribution at specific regions [23], [24]. However, there are several limitations in the VAT quantification using CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in elderly people have shown that fat free mass, muscle in the trunk and low extremity are associated with respiratory function9, 10, 25 ) . In addition, it has been reported that sarcopenia, an age-related reduction in muscle mass47 ) , causes breathing muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory function also decreases with age21, 22 ) and it is postulated that this is related to respiratory function and muscle mass. However, although studies for patients with COPD have shown that systemic inflammation and skeletal muscle disorders are associated with reduced physical activity23, 24 ) , there are limited reported studies on the association between respiratory function and muscle mass in the working age population in the abscence of COPD25 ) .…”
Section: Introductionmentioning
confidence: 99%